Identification of 4-4’-(1-methylethylidene)-bisphenol from an Endophytic Fungus Cladosporium oxysporum derived from Aglaia odorata - Armila Fatma Setyaningrum; Risma Pratiwi; Suciati Suciati; Noor Erma Nasution Sugijanto; Gunawan Indrayanto (UNIVERSITAS SEBELAS MARET (UNS), 2018)
Endophytic fungi has an economic potential as raw material for biologically active compounds. Cladosporium oxysporum is one of the endophytic fungi isolated from Indonesian medicinal plant Aglaia odorata Lour (Local name: Pacarcina). This planth has been used for fever, cough, diarrhea, inflammation and injury. In our previous study, the ethyl acetate extract and several fractions of the extract of C. oxysporum showed antimicrobial activity against Candida albicans, Escherichia coli, and Staphylococcus aureus. The objective of the currents study is to investigate the chemical constituent of the active fraction. Purification of the metabolite was achieved by using column chromatography followed by preparative thin layer chromatography. Identification of the metabolite was conducted by using TLC densitometry, GC-FID and GC-MS. Compound 1 was isolated from fraction 12. The purity of this compound was determined by 2D-TLC and GC-FID. The UV-Vis profile of compound 1 indicates a phenolic compound. Further analysis by using GC-MS shows one peak at a retention time (Rt) of 23.80 minutes, predicted as 4-4’-(1-methylethylidene)-bisphenol. The chemical constituent of the sub fraction 12.2.7 (fraction a) is identified as 4-4’-(1-methylethylidene)-bisphenol.